Pengolahan Air Limbah Untuk Pemanfaatan Penyiraman Tanaman di Hotel dan Restoran B Kota Surabaya - Tuhu Agung Rachmanto; Esha adiba (Prosiding ESEC, 2023)
A hotel B building that has been operating in the city of Surabaya generates domestic waste from lodging activities by hotel visitors and employees, restaurants and kitchens. The waste will be used for washing and watering in the Green Open Space which is at the back of the hotel with a total waste water produced of 7.52 m3/day. The resulting wastewater contains Ammonia, BOD, COD, Oil and Fat and coliform which exceeds the standard limits for the quality of wastewater so that it must be managed first before being used for watering plants in accordance with Regulation of the Minister of Environment and Forestry No. 68 of 2016 concerning Domestic Wastewater Quality Standards. The activity site has a grease trap, biofilter and WWTP unit which will be used for wastewater treatment to meet quality standards. The Green Open Space area is 10.5 m2 which will be used for the utilization of treated wastewater. The total volume of outlet water to be used for watering is 3.1 m3/day. Utilization of water can save PDAM water usage to support the production process or maintenance activities (watering the plants) around activity and/or business locations.